STRATEGI PEMBELAJARAN MEMBUAT POLA DRAPPING PADA SISWA TATA BUSANA DI SEKOLAH MENENGAH KEJURUAN - Raharjanti Raharjanti; Siti Mariah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2016)
The purpose of this study describes thelearning strategy of drilling pattern making in SMK,including:/ (1) planning; (2) implementation, (3)evaluation of learning outcomes and (4) obstaclesencountered in learning make draping patterns. Thedescriptive research used the qualitative method,with the subject of this research is teacher and student of class XI fashion at SMK MuhammadiyahImogiri Yogyakarta in academic year 2015/2016.Methods of data collection include:/ observation,interview, and documentation. Data validity usingtriangulation. Data analysis techniques include:/data reduction, data presentation, conclusion. andverification. The results showed: (1) Lesson planning is less effective, planning documents such asyearly and semester programs are incomplete, andless developed RPP. 2) Implementation of learningis good enough, shown the method of explaining,assignment, demonstration, and practice; Learningmedia using dummy equipped with job sheet andhandout to help students understand in making draping pattern. (3) Evaluation of learning outcomesmakes the draping pattern quite good, covering cognitive, affective, and psychomotor assessment with100% final grade students above the Maximum Exhaustiveness Criteria (KKM). (4) Obstacles or obstacles faced in learning make draping pattern thatis; Dense teacher work, lack of communication between teachers, and inadequate practice facilities sothat students use pass pop interchangeably